2021
DOI: 10.2147/ijn.s291956
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Factors Influences Biogenesis, Functions, Therapeutic and Clinical Implications of Exosomes

Abstract: Exosomes are nanoscale-sized membrane vesicles secreted by almost all cell types into the extracellular environment upon fusion of multivesicular bodies and plasma membrane. Biogenesis of exosomes is a protein quality control mechanism, and once released, exosomes transmit signals to other cells. The applications of exosomes have increased immensely in biomedical fields owing to their cell-specific cargos that facilitate intercellular communications with neighboring cells through the transfer of biologically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
194
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(197 citation statements)
references
References 321 publications
(210 reference statements)
1
194
0
2
Order By: Relevance
“…This technique was used broadly, alone or along with EM and other techniques, to study the properties, biological content, and identification markers of these smallest EVs, the exosomes. Extensive literature has revealed how exosomes can be identified by the expression of endosome tetraspanins (CD37, CD53, CD63, CD81, and CD82, among others), which are possibly responsible for cell penetration, invasion and fusion events [50,51]. Furthermore, in 2007 Valadi et al [52] showed that exosomes obtained from human mast cell line cultures, identified by ultracentrifugation and expression of CD63 by FACS analysis, contained RNA from approximately 1000 genes, many of which were not present in the cytoplasm of the donor cell.…”
Section: Exosomes or Microvesicles Or Extracellular Vesicles (Evs)mentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was used broadly, alone or along with EM and other techniques, to study the properties, biological content, and identification markers of these smallest EVs, the exosomes. Extensive literature has revealed how exosomes can be identified by the expression of endosome tetraspanins (CD37, CD53, CD63, CD81, and CD82, among others), which are possibly responsible for cell penetration, invasion and fusion events [50,51]. Furthermore, in 2007 Valadi et al [52] showed that exosomes obtained from human mast cell line cultures, identified by ultracentrifugation and expression of CD63 by FACS analysis, contained RNA from approximately 1000 genes, many of which were not present in the cytoplasm of the donor cell.…”
Section: Exosomes or Microvesicles Or Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Exosomes are different. It is well accepted that the "real" exosomes [51] are small EVs, which are formed by a process of inward budding in early endosomes, later forming multivesicular endosomes and eventually multivesicular bodies (MVBs) (Figure 3), which after fusion with the cell membrane release exosomes into the extracellular microenvironment to transfer their components [39,57].…”
Section: More Questions Than Answersmentioning
confidence: 99%
“…In addition to the above extrinsic biological factors, it is important that exosome biogenesis and uptake are also influenced by several external factors, such as cell type, cell state, hypoxia, serum conditions, the added cytokines and growth factors and even the separation and purification method of exosomes 35 . Targeting the biogenesis, release and uptake of exosomes might be a potential therapeutic approach to change the course of cancer.…”
Section: Factors Promoting Tumor-derived Exosome Biogenesis Release and Uptake For Bc Metastasismentioning
confidence: 99%
“…Besides the complexity of the transmitted message, EVs-mediated crosstalk is further regulated by their mode of action or internalization in recipient cells, including macropinocytosis, receptor-mediated endocytosis, phagocytosis or receptor-mediated signaling, which influences the ultimate fate of the transmitted information [ 10 ]. EVs are now reported as major actors of cellular crosstalk in physiological and physio-pathological contexts involving adaptive and responsive processes [ 11 ], which suggests that EVs’ production, secretion and uptake are part of a larger network of communication.…”
Section: Introductionmentioning
confidence: 99%